Reconstructing American historical cinema : from Cimarron to Citizen Kane - Smyth, J. E., 1977- (University Press of Kentucky, 2006)
Reconstructing American Historical Cinema explores Hollywood's pivotal interpretations of national history during the height of the studio system. In a radical departure from traditional studies of film and history, J.E. Smyth looks at rarely discussed production records and scripts from studio archives, arguing that certain classical Hollywood filmmakers were actively engaged in a self-conscious and often critical filmic writing of national history. Her unique approach unites the study of popular and academic historical writing, historical fiction, and screenwriting, providing a rich context.